Viscosity, density, and derived thermodynamic properties of aqueous 2-(ethylamino)ethanol (EAE), aqueous aminoethylethanolamine (AEEA), and its mixture for post-combustion CO2 capture - Pandey D.; Mondal M.K. (My University, 2025)
In the present study, viscosity and density of aqueous 2-(ethylamino)ethanol (EAE), aqueous aminoethylethanolamine (AEEA), and aqueous EAE + AEEA blend were measured in the temperature range of 293.15 K to 333.15 K at atmospheric pressure. Concentration of aqueous amines was used upto 30 wt% that is usually applicable for CO2 absorption from flue gases in post combustion CO2 capture process. EAE/AEEA weight ratio was 9/1, 8/2, and 7/3 in the aqueous EAE + AEEA blend. Viscosity of all mixtures increased by increasing amine concentration and decreased by increasing temperature of samples. Experimental viscosity data were correlated to newly proposed models and average absolute deviation (AAD) % was 1.515, 2.027, and 2.889 for viscosity of EAE + H2O, AEEA + H2O, and EAE + AEEA + H2O, respectively. Density of aqueous EAE and aqueous EAE + AEEA blend (at fixed EAE/AEEA weight ratio) decreased by increasing amount of amine in the mixture but aqueous AEEA showed increased density by increasing concentration of AEEA. Excess molar volume (VE) calculated for all aqueous mixtures and VE of aqueous EAE and aqueous AEEA was fitted in Redlich-Kister equation. Density of aqueous EAE + AEEA blend was correlated to a new empirical model and AAD % for this model was 0.018. Isobaric thermal expansion coefficient (αp) of binary and ternary solutions was calculated from density versus temperature data. Activation molar enthalpy (∆H∗), activation molar entropy (∆S∗), and activation molar Gibbs free energy (∆G∗) at 298.15 K for aqueous EAE, aqueous AEEA, and aqueous EAE + AEEA blend were calculated using viscosity and density data on the basis of Eyring theory of liquid viscosity. © 2021 Elsevier B.V.